2011
DOI: 10.1111/j.1742-7843.2011.00702.x
|View full text |Cite
|
Sign up to set email alerts
|

The Teratogenic Potencies of Valproic Acid Derivatives and Their Effects on Biological End‐points are Related to Changes in Histone Deacetylase and Erk1/2 Activities

Abstract: Valproic acid (VPA) is a known teratogen. In the present study, the effects of VPA and seven VPA derivatives with different teratogenic potencies were investigated in L929 cells in vitro. Evaluated end-points included changes in cell proliferation, growth, cell cycle distribution, morphology, speed, glycogen synthase kinase-3b (GSK-3b) and Erk1 ⁄ 2 phosphorylation, and histone H3 acetylation. Changes in proliferation, growth, speed, Erk1 ⁄ 2 and GSK-3b-Tyr216 phosphorylation, and H3 acetylation were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…Maximum histone H4 acetylation in HeLa cells appears nearly 12-16 h after VPA addition [6]. Acetylation of histone H3 also significantly increases in HeLa and L929 cells after VPA treatment [16], [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum histone H4 acetylation in HeLa cells appears nearly 12-16 h after VPA addition [6]. Acetylation of histone H3 also significantly increases in HeLa and L929 cells after VPA treatment [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the hyperacetylation of histones induced by a class I-specific HDAC inhibitor (HDACi) like VPA or by a pan-HDACi such as trichostatin A (TSA) [11] has been considered totally or at least partly responsible for the similar teratogenic side-effects in vertebrate embryos [1], [17], [22].…”
Section: Introductionmentioning
confidence: 99%
“…It was found the three strongest teratogens (i.e. butyl-, pentyl-and hexyl-4-yn-VPA) significantly increased the degree of histone H3 acetylation [Gotfryd et al, 2011]. These investigators observed a highly significant linear correlation between the teratogenic potencies of the test compounds and their effects on histone H3 acetylation (n = 42, R2 = 0.…”
Section: Phenobarbital (Solfoton)mentioning
confidence: 56%
“…These investigators observed a highly significant linear correlation between the teratogenic potencies of the test compounds and their effects on histone H3 acetylation (n = 42, R2 = 0. 5080, p < 0.0001) [Gotfryd et al, 2011].…”
Section: Phenobarbital (Solfoton)mentioning
confidence: 99%
“…The attention given to epigenetic mechanisms of VPA action arose from various studies demonstrating that VPA is a human teratogen. [98,99] Recently, it has been shown that VPA induces apoptosis and neural tube defects in postimplantation embryos. [100] A severe foetal valproate syndrome has also been documented.…”
Section: Epigenetic Characteristics Of Valproic Acidmentioning
confidence: 99%